Deep neuromuscular blockade for endolaryngeal procedures: A multicenter randomized study - Prok Laosuwan (2019)
© 2019 The American Laryngological, Rhinological and Otological Society, Inc. Objectives/Hypothesis: The aim of the present study was to compare the surgical condition between deep neuromuscular blockade (NMB) and moderate NMB. Study Design: Multicenter, randomized, parallel intervention trial. Methods: One hundred two patients underwent microscopic endolaryngeal surgery at four university hospitals. The patients were randomized into moderate NMB (train-of-four 1-2) (M group) or deep NMB (post-tetanic count 1-2) (D group) with moderate or high doses of rocuronium, respectively. Surgical rating conditions (SRCs) were evaluated during the surgery. Sugammadex was given to the M group at 2 mg/kg and the D group at 4 mg/kg. Perioperative clinical signs and conditions were recorded until discharge from the postanesthesia care unit. Results: Clinically acceptable SRC was observed in 49 patients (100%) in the D group and 43 patients (89.6%) in the M group (P =.027). The frequency of notable vocal fold movement in the M group was significantly higher than the D group (70.8% vs. 32.7%). The patients in the M group required more additional doses of rocuronium (47.9%) than the D group (20.4%) to maintain full relaxation (P =.005). The median time (interquartile range) from administration of sugammadex to train-of-four ratio 0.9 in the D group was shorter than the M group (120 [109–180 minutes] vs. 180 minutes [120–240 minutes], P =.034). Conclusions: Deep NMB with high doses of rocuronium combined with 4 mg/kg of sugammadex for reversal during endolaryngeal surgery provided better SRC and anesthetic conditions than moderate NMB of rocuronium with 2 mg/kg of sugammadex. Level of Evidence: 1b Laryngoscope, 2019.